Bioprinting in Regenerative Medicine - Manuela Monti (European Journal of Histochemistry, 2016)
Prof. Turksen is a very well known scientist in the stem cell biology field and he is also internationally known for his fundamental studies on claudin-6. In addition to his research activity he is editor for the Stem Cell Biology and Regenerative Medicine series (Humana Press) and editor-in-chief of Stem Cell Reviews and Reports.....